Outcomes of Autologous Blood Injection for Treatment of Tennis Elbow - Gupta, Mithilesh Kumar; Chaudhary, Ajay; Mahato, Ajay (Birat Journal of Health Sciences, 2022)
Introduction: Lateral tendinosis of the elbow, sometimes called tennis elbow, refers to the degenerative process in the common source of the extended group of forearm muscles. In orthopedic clinics, it is the most prevalent cause of elbow discomfort and pain. The condition caused by repeated muscular motions is a typical cause of elbow discomfort.Objectives: To assess the clinical and functional outcomes of autologous blood injection for the treatment of tennis elbow.Methodology: This is a hospital based cross-sectional study, conducted in Birat Medical College teaching hospital.  Here, the patients diagnosed with a Tennis elbow in orthopedic OPD during the study duration of September 2020 to August 2021 were included in the study. Total 93 samples were studied. Two ml of the patient's blood has withdrawn from the right antecubital vein and has been injected around the affected common extensor tendon origin. Data was analyzed using SPSS version 23.Results: Total Ninety Three (59% females, 41% male) patients were treated with the diagnosed concerned disease. The mean age of the patients was 45.39 ± 10.109 years. At the end of the trial, 90% of the patients were satisfied fully with the treatment. The overall performance of the regression model is significant in all scenarios.Conclusion: Given the satisfactory results, the blood injection in question can be deemed a suitable medication alternative to the conventional therapy.